Effects of Lycii Fructus and Salviae Miltiorrhizae on the Syndrome of Deficiency with Blood Stasis in RCS (rdy-/-, p-/-) Rats with Retinitis Pigmentosa: An Intervention Study - Xu Jian; Yang Yi-Jing; Qin Gen-Yan; Zhou Ya-Sha; Peng Jun; Peng Qing-Hua (KeAi Communications Co., Ltd., 2019)
Objective: To investigate the effects of Lycii Fructus (LF, Gou Qi Zi, 枸杞子) and Salviae Miltiorrhizae Radix Ex Rhizoma (SM, Dan Shen, 丹 参 ) on the syndrome of deficiency with blood stasis in the RCS (rdy-/-, p-/-) rats with retinitis pigmentosa (RP). Methods: A total of 32 RCS (rdy-/-, p-/-) rats were divided into 4 groups (equal amounts of female and male rats in each group): model group treated with 0.9% normal saline, LF group treated with LF formula granules, SM group treated with SM formula granules, and LF and SM (L·S) group treated with LF and SM formula granules. Eight RCS (rdy +/ +, p +/ +) rats (4 males and 4 females) were treated with 0.9% normal saline to serve as blank group. The contents of E2, PG, P-Selectin, plasma viscosity, whole blood relative index of the high shear rate and fibrinogen content in plasma, and the content of cAMP and cGMP in retinal homogenate were detected. The retina was evaluated by hematoxylin-eosin staining. Results: The contents of E2, PG, P-Selectin, plasma viscosity, whole blood relative index of the high shear rate, and fibrinogen content in the plasma of L·S group significantly differed from those of model group (P < 0.01), but were similar to those of blank group. The contents of cAMP and cGMP in the retinal homogenate of L·S group significantly differed from those in model group (P < 0.01) but were similar to those in blank group (P > 0.05). Conclusions: LF and SM can effectively treat retinitis pigmentosa by ameliorating the syndrome of deficiency with blood stasis. Keywords: Retinitis pigmentosa (RP), Lycii Fructus (Gou Qi Zi, 枸;杞;子;), Salviae Miltiorrhizae Radix Ex Rhizoma (Dan Shen, 丹;参;), Syndrome of deficiency with blood stasis, RCS (rdy-/-, p-/-) rat